Effectiveness of Cognitive Behavior Therapy and Psychotropic Medicines for Depression and Psychological Wellbeing in Patients with Depression - Rabia Yasmeen, Shazia Hassan (Pakistan Journal of Psychology, 2020)
This study investigated the effectiveness of CBT and psychotropic medicines for depression and psychological wellbeing in patients with depression. It also examined the difference in the treatment outcomes of psychotropic medicine alone as compared to CBT in combination with psychotropic medicines. The sample comprised of 50 male and female patients with depressive disorders out of which 25 patients received psychotropic medicines & 25 patients received CBT in combination with psychotropic medicines. The age of the sample ranged between 20-50 years recruited through purposive sampling. The quasi-experimental (Pretest-Posttest) design was employed. The results indicated that there was significant effect of both treatments on the patients of depression but combine treatment of CBT with psychotropic medication has more significant effect than the psychotropic medication alone. The study have implications and pave path for future investigation.